Study of Photophysico-chemical and Antimicrobial Photodynamic Properties of Visible Light Active Azometal(II) Complexes - Teja, H.B.; Bhojya Naik, H.S.; Amith Nayak, P.H.; Prabhakara, M.C. (Asian Journal of Chemistry, 2021)
The Co(II) and Mn(II) complexes with octahedral geometries of the type [Co(L)2(H2O)2] and [Mn(L)2(H2O)2] were synthesized and characterized by elemental analysis, FT-IR, UV-visible spectra, powered XRD and photoluminescence. Both metal(II) complexes were prepared with 4-[(Z)-(8-hydroxyquinolin-5-yl)diazenyl]-1,5-dimethyl-2-phenyl-1,2-dihydro-3H-pyrazol-3-one. The complexes were evaluated for in vitro antimicrobial photodynamic activity against Gram-positive, Gram-negative bacteria and fungi. The cell inhibition rate was found to be 80-96%. in vitro Cytotoxic studies were performed for the synthesized complexes against human melanoma (A-375) and human primary glioblastoma (U-87) cell lines by MTT assay where Co(II) complex showed potential inhibitory efficiency with IC50 value of 115 μg/mL when compared to Mn(II) complex.